Synthesis and characterization of silver/clay/chitosan bionanocomposites by UV-irradiation method - Ahmad, Mansor; Shameli, Kamyar; Darroudi, Majid; Wan Yunus, Wan Md. Zin; Ibrahim, Nor Azowa (Science Publications, 2009)
Problem statement: Silver/Montmorillonite/Chitosan Bionanocomposites (Ag/MMT/Cts BNCs) have been synthesized by UV-irradiation reduction method in the absence of any reducing agent or heat treatment which is used to antibacterial application and medical devices. Approach: MMT, Chitosan and AgNO3 were used as a solid support, stabilizer and silver precursor, respectively. The properties of Ag/MMT/Cts BNCs were studied as a function of UV-irradiation times. The crystalline structure, d-spacing of interlayer of MMT, the size distributions and surface plasmon resonance of synthesized silver nanoparticles (Ag-NPs) were characterized using Powder X-Ray Diffraction (PXRD), Transmission Electron Microscopy (TEM) and UV-vis spectroscopy. The functional groups of prepared BNCs were also determined by Fourier Transform Infrared (FT-IR). Results: The results obtained from UV-vis spectroscopy of synthesized Ag-NPs showed that the intensity of the maximum wavelength of the plasmon peaks were increased with the increasing in the UV-irradiation times. Results from UV-visible spectroscopy and Transmission Electron Microscopy (TEM) microphotographs show that particles size of Ag-NPs decrease with the increase of UV-irradiation time. Conclusion: UV-irradiation disintegrated the Ag-NPs into smaller size until a relatively stable size and size distribution were achieved. Ag/MMT/Cts BNCs could be suitable to antimicrobial applications and medical devices.